ACCURACY OF VISUAL INSPECTION WITH ACETIC ACID FOR CERVICAL LESIONS: A SYSTEMATIC REVIEW AND METAANALYSIS - Faris Regi Riswana; Faris Rega Riswana; Krisjentha Iffah Agustasari; Nabila Khairunisa Azzahra; Amanda Fransisca Rhevytasari (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Visual inspection with acetic acid (VIA) remains widely used for cervical cancer screening in low- and middle-income countries, despite ongoing concerns regarding its diagnostic accuracy. This study aimed to evaluate the diagnostic performance of VIA for detecting high-grade cervical lesions (CIN2+) compared with histopathology. A systematic search was conducted in PubMed, Scopus, and ScienceDirect (2015–October 2025). Eligible studies provided sufficient data to construct 2×2 tables and were assessed using QUADAS-2. A bivariate random-effects model and HSROC analysis were applied. Thirteen studies were included, with five eligible for quantitative synthesis. Sensitivity ranged from 0.25 to 0.92 and specificity from 0.49 to 0.97, indicating substantial heterogeneity. Risk of bias was generally low to moderate, mainly in patient selection and flow and timing domains. VIA demonstrates moderate accuracy with variability across populations. Although less sensitive than HPV-based screening, VIA remains a pragmatic option in resource-limited settings, particularly within screen-and-treat strategies, with strengthened training and quality assurance required